Trends in peripheral artery disease and critical limb ischemia hospitalizations among cocaine and methamphetamine users in the United States: a nationwide study - Ali, Shafaqat; Al-Yafeai, Zaki; Hossain, Md. Ismail; Bhuiyan, Md. Shenuarin; Duhan, Sanchit; Aishwarya, Richa; Goeders, Nicholas E.; Bhuiyan, Md. Mostafizur Rahman; Conrad, Steven A.; Vanchiere, John A.; Orr, A. Wayne; Kevil, Christopher G.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Peripheral artery disease (PAD) is on the rise worldwide, ranking as the third leading cause of atherosclerosis-related morbidity; much less is known about its trends in hospitalizations among methamphetamine and cocaine users. Objectives: We aim to evaluate the overall trend in the prevalence of hospital admission for PAD with or without the use of stimulant abuse (methamphetamine and cocaine) across the United States. Additionally, we evaluated the PAD-related hospitalizations trend stratified by age, race, sex, and geographic location. Methods: We used the National Inpatient Sample (NIS) database from 2008 to 2020. The Cochran Armitage trend test was used to compare the trend between groups. Multivariate logistic regression was used to examine adjusted odds for PAD and CLI hospitalizations among methamphetamine and cocaine users. Results: Between 2008 and 2020, PAD-related hospitalizations showed an increasing trend in Hispanics, African Americans, and western states, while a decreasing trend in southern and Midwestern states (p-trend<0.05). Among methamphetamine users, an overall increasing trend was observed in men, women, western, southern, and midwestern states (p-trend<0.05). However, among cocaine users, PAD-related hospitalization increased significantly for White, African American, age group >64 years, southern and western states (p-trend<0.05). Overall, CLI-related hospitalizations showed an encouraging decreasing trend in men and women, age group>64 years, and CLI-related amputations declined for women, White patient population, age group >40, and all regions [p-trend <0.05]. However, among methamphetamine users, a significantly increasing trend in CLI-related hospitalization was seen in men, women, White & Hispanic population, age group 26-45, western, southern, and midwestern regions. Conclusions: There was an increasing trend in PAD-related hospitalizations among methamphetamine and cocaine users for both males and females. Although an overall decreasing trend in CLI-related hospitalization was observed for both genders, an up-trend in CLI was seen among methamphetamine users. The upward trends were more prominent for White, Hispanic & African Americans, and southern and western states, highlighting racial and geographic variations over the study period.